Comparative biogeography and the evolution of population structure for bottlenose and common dolphins in the Indian Ocean. (4th May 2021) - Gray, Howard W. I.; Chen, Ing; Moura, André E.; Natoli, Ada; Nishida, Shin; Tanabe, Shinsuke; Minton, Gianna; Ponnampalam, Louisa S.; Kiani, Muhammad S.; Culloch, Ross; Gore, Mauvis; Särnblad, Anna; et al.
Abstract: Aim: In the marine environment, where there are few physical boundaries to gene flow, there is often nevertheless intraspecific diversity with consequences for effective conservation and management. Here, we compare two closely related dolphin species with a shared distribution in the Indian Ocean (IO) to better understand the biogeographic drivers of their population structure. Location: Global oceans and seas with a focus on the Indian Ocean Taxon: Tursiops sp. and Delphinus sp. Methods: Bayesian, ordination, assignment, statistical and phylogenetic analyses to assess phylogeography, connectivity and population structure using microsatellite and mitochondrial DNA genetic markers. Results: Both Tursiops sp. and Delphinus sp. showed population structure across the western IO and, in each case, populations in the Arabian Sea (off India, Pakistan and Oman) were most differentiated. Comparisons with other populations worldwide revealed independent lineages in this geographic region for both genera. For T . aduncus, (for which multiple sites within the IO could be compared), Bayesian modelling best supported a scenario of expansion southwards following a bottleneck event resulting in differentiation between the northern and western IO. For Delphinus, the same pattern is even more pronounced. Populations in the Arabian Sea region of the north‐western IO show genetic isolation for each of the two genera, consistent with other studies of cetacean species in this region. Main conclusions: We propose that changes in the intensity of the southwest monsoon during the climate cycles of the Pleistocene could have affected regional patterns of productivity and represent an important biogeographic driver promoting the observed patterns of differentiation and population dynamics seen in our focal species. Patterns of population genetic structure are consistent with phenotypic differences, suggesting an influence from distinct habitats and resources, and emphasising the need for effective conservation measures in this geographic region.